2017
DOI: 10.1136/bmjopen-2017-018829
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of hypertension in Northern Tanzania: a community-based mixed-methods study

Abstract: IntroductionSub-Saharan Africa is particularly vulnerable to the growing global burden of hypertension, but epidemiological studies are limited and barriers to optimal management are poorly understood. Therefore, we undertook a community-based mixed-methods study in Tanzania to investigate the epidemiology of hypertension and barriers to care.MethodsIn Northern Tanzania, between December 2013 and June 2015, we conducted a mixed-methods study, including a cross-sectional household epidemiological survey and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 36 publications
5
57
1
1
Order By: Relevance
“…Interestingly, a much higher prevalence (49.1%) of hypertension was reported among 513 adults in a rural setting in Madagascar [12]. Conversely, a lower rate (28.0%) of hypertension was reported in Tanzania [13] and in a population-based sectional study that enrolled 67,397 participants in Ethiopia (31.9%) [24]. In neighbouring Ethiopia, while a low rate (10.5%) of hypertension was reported in a hospital-based study [8], a prevalence rate of 34.7% for hypertension was reported in the capital, Addis Ababa [10].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, a much higher prevalence (49.1%) of hypertension was reported among 513 adults in a rural setting in Madagascar [12]. Conversely, a lower rate (28.0%) of hypertension was reported in Tanzania [13] and in a population-based sectional study that enrolled 67,397 participants in Ethiopia (31.9%) [24]. In neighbouring Ethiopia, while a low rate (10.5%) of hypertension was reported in a hospital-based study [8], a prevalence rate of 34.7% for hypertension was reported in the capital, Addis Ababa [10].…”
Section: Discussionmentioning
confidence: 93%
“…Because of our study design (controlled for age), it might not be valid to compare our results (age and hypertension) with the results of the large study that was recently conducted in four states (Khartoum, Gezira, Blue Nile and Kassala) in Sudan [15]. Several studies have shown that an older age is significantly associated with hypertension in neighbouring countries, including Ethiopia [8,9,11], Tanzania [13] and Madagascar [12]. Similarly, a recent metaanalysis including 43,025 older adults (> 53 years) in 15 African countries showed that an older age is independently associated with hypertension [25].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study was conducted in the ED at Kilimanjaro Christian Medical Center (KCMC), a tertiary care center in Moshi, Tanzania. In 2014, the local prevalence of hypertension and diabetes was estimated to be 28% and 6%, respectively [10,29]. KCMC has multiple electrocardiogram (ECG) machines, and the laboratory can perform laboratory-based assays for troponin I and troponin T. KCMC has capacity for thrombolytic therapy, but does not presently have capacity for cardiac catheterization or stress testing.…”
Section: Study Settingmentioning
confidence: 99%
“…В Южной Америке в кросс-секционном национальном исследовании в Бразилии (2018) распространенность АГ составила 32,3% (95% ДИ 31,7-33,0) [26]. Распространенность АГ в Африке в Танзании (2017) составляла 28,0% [27]. Распространенность АГ была самой низкой в сельской Индии (3,4% у мужчин и 6,8% у женщин) [28].…”
unclassified